A Road Map for the Development of the Bleached Coral Phenotype - Gómez-Campo, Kelly; Enríquez, Susana; Iglesias-Prieto, Roberto (Frontiers in Marine Science, 2022)
Mass coral bleaching compromises the long-term persistence of coral reefs, yet our current understanding of the different cellular mechanisms leading to the development of a bleached coral is still limited. In this perspective, we mapped the cascade of cellular events and physiological responses of symbiotic corals triggered by thermal stress. Based on existing knowledge, we created an integrated model that describes phenotypic changes induced by sensing mechanisms. Cellular responses are mapped in the context of reactive oxygen species (ROS) production in the algal symbiont chloroplast, followed by signaling to the nucleus and subsequent “leak” to the coral host cell. The starting point is set by ROS production and signaling, which is a day-to-day mechanism by which symbiotic corals maintain homeostasis and acclimate to environmental variation. As stress and acclimation are intimately linked, our model maps coral responses from the initial stimulus in the chloroplast to the complex cascade of events leading to seasonal phenotypic changes (i.e., seasonal acclimation), and if stress progresses, to the downstream coral bleached phenotype (i.e., when the coral’s capacity to acclimate is overwhelmed by heat stress). Placing acclimation, heat stress and bleaching responses in a common ground is a critical step to reduce the source of uncertainty in understanding the coral response to climate change, fundamental for the development of predictive climate models.